Enhancement of nurse scheduling steps using particle swarm optimization - Mohd Rasip, Norhayati; Hasan Basari, Abd Samad; Ibrahim, Nuzulha Khilwani; Hussin, Burairah (2014)
Allocation of working schedule especially for shift approach is hard to ensure its fairness among them. In the case of nurse scheduling, to set up the time tablefor each available nurse is time consuming and complicated, which consider many factors including rules, regulation and human factor. Moreover, most nurses are women which have personnel constraints and maternity leave factors. The undesirable schedule can affect the nurse productivity, social life and the absenteeism can significantly as well affect patient's life. This paper aimed to enhance the scheduling process by utilizing the particle swarm optimization in order to generate an intelligent nurse schedule. The result shows that the multiple initial schedule can be generated and can be selected with the lowest cost of constraint violation.